KUTTAB DALAM LINTASAN SEJARAH : DARI MASA PEMBINAAN HINGGA KEJAYAAN PENDIDIKAN ISLAM (570 M-1258 M) - Mahfud Ifendi (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2021)
Kuttab is an Islamic educational institution that appeared at the beginning of Islamic civilization. Actually, its existence has been known since pre-Islamic time, but its development it has not gone well. In order to describe the kuttab in some time, in this article data were collected from various works of literature such as scientific articles, historical books, and research results. The data analysis used data analysis by Miles and Hubberman. In conclusion, this article shows that kuttab in the trajectory of Islamic history has undergone several reforms, both in terms of management, financing, and curriculum. From the curriculum content, there are several striking updates that we can observe in each period. Starting from the simplest teaching about reading and writing to Muslim children to the middle and high levels there are lessons on balaghah, nahwu, sharaf, mantiq, tafsir, fiqih, ushul fiqh, medicine, chemistry, zoology, and others. Regarding financing, some are voluntary, from land taxes and officially taken from the state budget